2015
DOI: 10.1002/stem.2079
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Innate Immunity in Embryonic Stem Cells and Its Implications in Developmental Biology and Regenerative Medicine

Abstract: Embryonic stem cells (ESCs) represent a promising cell source for regenerative medicine. Intensive research over the past two decades has led to the feasibility of using ESC-differentiated cells (ESC-DCs) in regenerative medicine. However, increasing evidence indicates that ESC-DCs generated by current differentiation methods may not have equivalent cellular functions to their in vivo counterparts. Recent studies have revealed that both human and mouse ESCs as well as some types of ESC-DCs lack or have attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 97 publications
6
32
0
Order By: Relevance
“…Our data from hESCs clearly illustrate that they are similar to mESCs in the lack of NFκB activation and inflammatory response to LPS and TNFα. These results are also in accordance with the fact that both mESCs and hESCs are deficient in the expression of type I IFN in antiviral response, which is an NFκB-dependent process (10). Considering the highly conserved role of NFκB in innate immunity among different species of vertebrates (40), our findings suggest that the lack of NFκB activation in response to immune and inflammatory stimuli is likely an intrinsic property of both hESCs and mESCs.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Our data from hESCs clearly illustrate that they are similar to mESCs in the lack of NFκB activation and inflammatory response to LPS and TNFα. These results are also in accordance with the fact that both mESCs and hESCs are deficient in the expression of type I IFN in antiviral response, which is an NFκB-dependent process (10). Considering the highly conserved role of NFκB in innate immunity among different species of vertebrates (40), our findings suggest that the lack of NFκB activation in response to immune and inflammatory stimuli is likely an intrinsic property of both hESCs and mESCs.…”
Section: Discussionsupporting
confidence: 86%
“…Many other functions, such as innate immunity, cannot be assessed unless the cells are exposed to pathogens. Recent studies have reported that several major tissue cell types differentiated from both human and mouse ESCs have limited innate immune response to various pathogens and cytokines (49), highlighting the potential functional deficiency of in vitro ESC-differentiated cells, as we have recently discussed (10). …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Therefore, the IFN system, which is the central part of innate immunity in differentiated somatic cells [14], is not fully functional in ESCs. Together with the similar findings in induced pluripotent stem cells [15] and embryonal carcinoma [16], an underdeveloped antiviral innate immunity represents an intrinsic property of all pluripotent cells (reviewed in Guo et al [17]). …”
Section: Introductionmentioning
confidence: 62%
“…The underdeveloped innate immunity has been recently characterized as a unique property of pluripotent cells as we have recently discussed (reviewed in Guo et al [17]). Since most types of somatic cells have an effective innate immune system, the attenuated immune and inflammatory responses reported in several ESC-derived tissue cells [3][4][5][6] raise the question of whether the commonly used in vitro differentiation methods can generate cells with competent innate immunity like in vivo differentiated cells.…”
Section: Discussionmentioning
confidence: 99%